PENERAPAN MODEL PEMBELAJARAN STAD BERBANTUAN QUIZIZZ PAPER MODE PADA SISWA KELAS VIII SMP - Dea Tiara; Dodik Mulyono; Lucy Asri Purwasi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to determine the mathematics learning outcomes of class VIII students of SMP IT Annida Lubuklinggau after the application of the STAD model assisted by Quizizz Paper Mode. The research method uses a quasi-experimental method (Pre-Experimental Designs) in the form of One-Group Pre-test-Post-test Design. The population of this study was all class VIII students of SMP IT Annida Lubuklinggau and the research sample was class VIII.3. The data collection technique was in the form of 5 essay questions. The data analysis technique used the t-test. The results of the study showed that the average mathematics learning outcomes of class VIII students of SMP IT Annida Lubuklinggau after the application of the Student Teams Achievement Division (STAD) model assisted by Quizizz Paper Mode were significantly complete. The results of the calculation of the Pre-test mathematics learning outcomes obtained an average value of 41.77 while the results of the calculation of the Post-test obtained an average value of 77.14. Based on the t-test analysis, it was obtained that  tcount = 4.35 with a significance level of α = 5% or α = 0.05 obtained ttable = 2,045, this shows that  tcountttable, namely 4.35 2,045, so it can be concluded that the implementation of the Student Teams Achievement Division (STAD) model assisted by Quizizz Paper Mode was significantly complete.